개인정보보호법의 개관 및 개정방향에 관한 연구 - 김일환; Ilhwan Kim; 성재호; Jaeho Sung (Inteonet jeongbo hakoe nonmunji = Journal of Korean Society for Internet Information, 2015)
2011년 3월 제정된 개인정보보호법은동 법의 적용대상을 공공·민간부문의 모든 개인정보처리자로하고 개인정보의 수집, 이용, 제공 등 단계별 보호기준을 마련하였다. 프라이버시 영향평가를 도입하여 일정한 경우 개인정보처리자가 자동적으로 영향평가를 수행 하도록 하고 있는 등 개인정보보호법의 전체적 취지와 내용은 높이 평가할 수 있으나, 여전히 전체적으로 어렵고 이해하기 쉽지 않다는 문제점을 안고 있다. 특히 법조문의 불명확성이나 해석, 개인정보보호법상 추진체계 등에 문제가 있으므로, 본고에서 이러한 문제점 등에 대해 고찰해 본다. The Personal Information Protection Act enacted in March 2011 stated that the application target of this law includes all personal information processors in the public and private sector, and established the protection standard by phase such as collection, use and provision of personal information. There was an introduction of the Privacy Impact Assessment system that enables personal information processors to perform impact assessment autonomously if there are great concerns over the fact that making and expanding personal information files will influence the protection of personal information, while also making impact assessment compulsory for public institutions in specific reasons with great concerns for violating the rights of the subjects of information. This Act still has the problem that it is generally difficult to understand.This paper deals with the Korean legal practices about the personal information protection with regard to ambiguity and promotional system.